Investigation of Correction Methods for Interference Effects in Open-Jet Wind Tunnels - Fischer, Oliver (Wissenschaftliche Reihe Fahrzeugtechnik Universität Stuttgart,, 2018)
Oliver Fischer analyzes the interference effects occurring in free-stream wind tunnels as well as their correction and simulation. With this work, the investigated correction method and the comparability of its results as well as flow simulation results are improved. The model wind tunnel of the IVK, University of Stuttgart, is simulated in various wind tunnel configurations. The application of a correction procedure to the corresponding experimental data from the model wind tunnel of the IVK is examined. These correction results are directly comparable with interference-free simulation results and thus allow a conclusion on the functionality of the correction method. Based on these findings, this thesis proposes a modification of the correction method that improves the comparability of corrected experimental results and CFD simulations in idealized test conditions. Contents Wind Tunnel Interference Effects Correction Method and Computational Fluid Dynamics Investigations Application and Investigation of the Correction Method Target Groups Researchers and students of mechanical engineering, especially automotive engineering Research and development engineers in the fields of aerodynamics and wind tunnel technology About the Author Oliver Fischer works as an engineer in aerodynamics development for a renowned German automobile manufacturer.